2010
DOI: 10.1124/jpet.109.163568
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Receptor-Mediated Elimination of Erythropoietin by Analysis of Erythropoietin Receptor mRNA Expression in Bone Marrow and Erythropoietin Clearance During Anemia

Abstract: Erythropoietin (Epo) is the primary hormone that stimulates erythroid proliferation and differentiation through its cell surface receptor (EpoR) on erythroid progenitor cells. Previous studies have suggested that the bone marrow plays an important role in Epo's elimination. The changes in the EpoR mRNA levels and Epo's clearance in the bone marrow of 11 newborn lambs were studied to elucidate the role of EpoR in Epo's clearance under anemic conditions. Epo mRNA levels were measured by realtime polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 27 publications
4
38
0
Order By: Relevance
“…In addition, because the EpoRs are located primarily in the bone marrow, phlebotomy does not significantly change the EpoR pool. Our group recently showed that EpoR mRNA is up-regulated after the induction of anemia in sheep, which is consistent with the model used in this study (Nalbant et al, 2010). Because this study used the GAPDH gene as a control, it can be suggested that the number of EpoRs per cell increased rather than the total number of cells.…”
Section: Erythropoietin Efficacy Dosing Optimizationsupporting
confidence: 68%
See 1 more Smart Citation
“…In addition, because the EpoRs are located primarily in the bone marrow, phlebotomy does not significantly change the EpoR pool. Our group recently showed that EpoR mRNA is up-regulated after the induction of anemia in sheep, which is consistent with the model used in this study (Nalbant et al, 2010). Because this study used the GAPDH gene as a control, it can be suggested that the number of EpoRs per cell increased rather than the total number of cells.…”
Section: Erythropoietin Efficacy Dosing Optimizationsupporting
confidence: 68%
“…An additional study modeled the change in the EpoR level over time after the induction of anemia (Chapel et al, 2001). In a recent study by our group, we reported up-regulation of EpoR mRNA levels of 4.97 Ϯ 3.92 times baseline at 9 days after the induction of anemia (Nalbant et al, 2010). Although EpoR mRNA levels do not necessarily correlate directly with the number of receptors, an increase in the mRNA level is probably associated with an increase in the quantity of EpoRs.…”
Section: Introductionmentioning
confidence: 99%
“…57 Similar to previous neonatal studies, 28,29,58,59 we found that high- Epo appears to be primarily eliminated by receptor-mediated clearance. 31,62 As in previous reports, 32,33,58,63 we found that Epo followed nonlinear pharmacokinetics. As the dose of Epo increased twofold, fourfold, and 10-fold, the overall exposure to circulating Epo (AUC) increased 2.7, 7.1, and 17.8 times, respectively.…”
Section: Figuresupporting
confidence: 68%
“…1318, 33, 34 Nalbant et al 15 demonstrated the relationship between EPOr expression and anemia. They demonstrated a 12-fold increase in bone marrow EPOr levels nine days post phlebotomy (Hb: 3.7–4.2 g/dL) when compared to pre-phlebotomy (Hb: 9.7±1.1 g/dL).…”
Section: Discussionmentioning
confidence: 99%
“…1318 Although EPOr is located on multiple cell types, it is mainly found within bone marrow on erythroid progenitor cells such as burst-forming unit erythroid (BFU-Es) and colony-forming unit erythroid cells (CFU-Es). 15 Specifically, the binding between EPOr and EPO is required for the proliferation and survival of CFU-Es to produce mature erythrocytes. 1618 Previous work has shown that serum EPO levels are significantly elevated following burns and trauma.…”
Section: Introductionmentioning
confidence: 99%